Perubahan Makna Cidera Janji atau Wanprestasi pada Jaminan Fidusia Setelah Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Dwi Prilia, Ega; Suphia, Suphia; Supianto, Supianto (WELFARE STATE Jurnal Hukum, 2023)
A debtor who feels aggrieved then submits a judicial review of the validity of Article 15 paragraphs (2) and (3) of Law no. 42 of 1999 which are considered to have violated the debtor's constitutional rights so that the Constitutional Court Decision No. 18/PUU-XVII/2019. Requirements for the debtor to be declared in breach of contract in the fiduciary guarantee after the decision of the Constitutional Court Number 18/PUU-XVII/2019, namely the breach of contract as referred to in Article 15 paragraph (3) of the Fiduciary Guarantee Law is not determined unilaterally by the creditor but on the basis of an agreement between creditors and debtors or on the basis of a legal remedy that determines that a breach of contract has occurred. Legal considerations of the Constitutional Court in deciding case No. 18/PUU-XVII/2019 is based on legal considerations that the norms contained in Article 15 paragraph (2) of the Fiduciary Guarantee Law do not reflect the existence of equal legal protection between parties bound in fiduciary agreements that are directly related to the norms of Article 15 paragraph (3) The Fiduciary Guarantee Law, namely the absence of legal certainty regarding when the debtor can be declared in breach of contract.